Robert Mackay Fripp in the 1890s: Peripatetic Pacific Rim Architect - Milojevic, Michael (Architectural History Aotearoa, 2007)
When the 30-year old English-born, Auckland-trained Robert Mackay Fripp (1858-1917) and his New Zealand bride left the port of Auckland in the late summer of 1888, they were headed for the bustling construction environment of post-fire Vancouver. Leaving his practice with C Paul, and his architectural design tutorship at the Auckland Society of the Arts, Fripp's was an astute career move. In the not quite eight years Fripp was based in Vancouver, he built and published almost 50 projects in British Columbia before he escaped the fast-approaching Vancouver recession and returned to Auckland in 1896. Attempting to put himself forward for more prestigious commissions in the Lower Mainland and Vancouver Island (which regularly went to Samuel Maclure), Fripp developed a national profile as an Arts and Crafts aesthete and designer with considerable international experience by publishing his drawings and reporting on the "West Coast scene" in the Toronto-based Canadian Architect and Builder (CAB). Among the local-interest articles there, which he consistently turned into a crabby proselytising for the Arts and Crafts, Fripp also placed both appreciative and critical articles and notes on Māori architecture and domestic design, and timber and construction in Auckland, and, even more surprisingly, he continued to do so throughout the 1890s, that is, long after he returned to New Zealand and set-up in partnership with GS Goldsboro' in Auckland. Meanwhile in the 33 months Fripp was back in Auckland from 1896 he realised a number of substantive and significant Auckland houses in Parnell, Grafton and Mount Eden. In these works I will show that he can be seen to have brought current "progressive" ideas from the West Coast about strongly-shaped shingled and half-timbered houses simply detailed with heavy timber to stand within the strong ocean coastal conditions. Fripp left for Victoria in 1899 and after some disappointing (losing the competition for Government House to Francis Rattenbury) months, during which he posted a scathing report in CAB about house design in Auckland, he moved to Los Angeles renting office space immediately adjacent to the Greene brothers executing and publishing a series of large (as yet undiscovered) houses in and around Santa Monica and Pasadena throughout 1900-5.